Differential Gene Expression and Biological Analyses of Primary Hepatocytes Following D-Chiro-Inositol Supplement - Cheng, Feier; Yun, Shao-jun; Cao, Jin-ling; Chang, Ming-chang; Meng, Jun-long; Liu, Jing-yu; Cheng, Yan-fen; Feng, Cui-ping (Frontiers in Endocrinology, 2021)
Dietary supplements have improved the prevention of insulin resistance and metabolic diseases, which became a research hotspot in food science and nutrition. Obesity and insulin resistance, caused by a high-fat diet, eventually result in severe metabolic diseases, can be prevented with the dietary supplement D-chiro-inositol (DCI). In this work, we isolated mice primary hepatocytes with palmitic acid stimulation and DCI was applied to compare and contrast its effects of in primary hepatocyte biology. Before and after intervention with DCI, we used RNA-Seq technology to establish a primary hepatocyte transcriptome gene profile. We found that both PA and DCI cause a wide variation in gene expression. Particularly, we found that DCI plays critical role in this model by acting on glycolysis and gluconeogenesis. Overall, we generated extensive transcripts from primary hepatocytes and uncovered new functions and gene targets for DCI.